Analisis Implementasi Hubungan Sekolah dengan Wali Murid dalam Peningkatan Akhlak Siswa di Sekolah Penggerak - Santi, Yulia; Yeni, Ety Mukhlesi; Marisa, Riandi (Ahdāf: Jurnal Pendidikan Agama Islam, 2023)
This study aims to analyze the implementation of parent-school relationships in enhancing student moral development at SD Negeri 12 Bireuen, operating as a Sekolah Penggerak. The research employs a descriptive qualitative approach and encompasses various stakeholders, including the principal, teachers, students, parents, school committee, and the school environment. Data was gathered through observation, interviews, and documentation. The analysis focuses on the principal's leadership role in engaging with the community within the context of the Sekolah Penggerak in Bireuen Regency, following the steps of data collection, reduction, presentation, and conclusion. The findings reveal that the approach adopted by the Principal of SD Negeri 12 Bireuen has fostered an environment conducive to positive moral growth among students. Collaborative efforts and participation from diverse groups, such as the teachers' council, committees, parents, and community leaders, have proven pivotal in program planning and execution. Utilizing both group and individual meetings, alongside mediums like brochures, newsletters, and the Monday flag ceremonies, has effectively strengthened the school's community relationships and facilitated the dissemination of student and school-related information. An encompassing evaluation of various school elements underscores the program's success in enhancing student morale. In summary, the integration of parent-school relations within the framework of Sekolah Penggerak has yielded constructive outcomes on student moral development. The principal and the school community have effectively cultivated cooperative partnerships, promoted robust communication, and ensured active engagement from all stakeholders.